The Effect of Private Inflation and Investment on Unemployment and Poverty in North Maluku Province - Nonce Hasan; Muammil Sun'an (Journal of International Conference Proceedings (JICP), 2020)
Poverty refers to a person's inability to get a stable livelihood and provide a decent income to support his/her life in a sustainable manner. Poverty is a problem deserving undivided attention in any country. Poverty is triggered by various factors, including low investment levels, high unemployment rates, and slow economic growth. This study aims to: 1) determine the effect of inflation rate and private investment on the unemployment rate; 2) determine the effect of inflation rate and private investment on poverty level; and 3) determine the effect of unemployment rate on poverty level. This study uses time series data from 2012 to 2018 and path analysis. The findings indicate that inflation has a positive effect on unemployment and poverty, and the level of private investment has a negative effect on unemployment and poverty.